Design and validation of a multimodal low-budget Raman-microscope for liquid and solid phase applications - Will, Stefan; Koch, Hanna; Noack, Kristina (Optical Methods for Inspection, Characterization, and Imaging of Biomaterials II, 2015)
Confocal Raman microscopy is a powerful tool to measure small sample volumes or solids. Since commercial Raman microscopes are expensive and a change of the laser wavelength or the excitation path is hardly possible after the installation, we constructed a multimodal low-budget Raman microscope. Thus, it was possible to significantly increase the flexibility in terms of excitation wavelengths, paths, and planes. Furthermore, the asset costs were reduced by a factor of 1.7. By using commercial as well as home-built objectives to adapt the working distance and the magnification to the system under investigation, the self-constructed Raman microscope offers the possibility to measure big sample volumes, too. The obtained Raman spectra were validated by Raman spectra from a commercial Raman microscope. With a comparable measurement setting it was possible to increase the signal intensities, but with a slightly lower SNR. However, based on the great flexibility of the set-up, e.g., the laser power or the excitation wavelength can be adapted to increase the SNR. Furthermore, measurement times can be decreased. With this low-budget self-constructed Raman microscope high quality Raman microscopy and micro spectroscopy can be performed with a high flexibility to fast adapt the set-up to the sample under investigation which is not offered by commercial microscope
Keywords: Raman microscope; low-budget; confocal; validation; multimodal; application-oriented

Experimentelle und theoretische Untersuchung optisch aktiver Moleküle zur Online-Analyse der Enantiomertrennung mittels Raman-Spektroskopie - Noack, Kristina; Koch, Hanna; Kiefer, Johannes; Kaspereit, Malte; Will, Stefan (ProcessNet-Jahrestagung 2014, 2014)

Investigating the moisture content of polyamide 6 by Raman-microscopy and multivariate data analysis - Lechner, Tobias; Noack, Kristina; Thöne, Manuel; Amend, Philipp; Schmidt, Michael; Will, Stefan (2016)
Dedicated to Professor Alfred Leipertz on the occasion of his 70th birthday. (C) 2016 Published by Elsevier B.
Keywords: moisture content; polyamide; Raman-microscopy; multivariate data analysis

Raman excess spectroscopy vs. principal component analysis: Probing the intermolecular interactions between chiral molecules and imidazolium-based ionic liquids - Will, Stefan; Koch, Hanna; Noack, Kristina (Physical Chemistry Chemical Physics, 2016)
Raman spectroscopy is a very sensitive and specific measurement tool for probing intermolecular interaction structures. As imidazolium-based ionic liquids can favorably be used for enantioseparation, in this work two approaches for Raman signal analysis, namely by means of excess spectra and principal component analysis (PCA), are compared to extract detailed information about the interaction structure of the enantiomers d- and l-glucose in an aqueous solution of the ionic liquid [EMIM][EtSO]. In contrast to the excess calculations, the loadings obtained from PCA lead to significant results since the interactions are weighted by their strength and significance. Moreover, the analysis of the weighted vibrations in the loadings indicate that hydrogen bonds are particularly formed between the ethyl sulphate anion of [EMIM][EtSO] and the hydrogen atom of the OH-group at the C-atom of glucose.

Raman Spectrocopy for non-invasive online measuerements of the pH and CO2 concentration in algal cultivations - Koch, Hanna; Noack, Kristina; Stute, Stephanie; Buchholz, Rainer; Will, Stefan (3rd European Congress of Applied Biotechnology (ECAB), 2015)

The role of the C2 position in interionic interactions of imidazolium based ionic liquids: a vibrational and NMR spectroscopic study - Noack, Kristina; Schulz, Peter; Paape, Natalia; Kiefer, Johannes; Wasserscheid, Peter; Leipertz, Alfred (Physical Chemistry Chemical Physics, 2010)
Methylation of the C2 position of 1,3-dialkylimidazolium based ionic liquids disrupts the predominant hydrogen-bonding interaction between cation and anion leading to unexpected changes of the physicochemical properties. We found the viscosity of 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide [C2C1C1Im][Tf2N], for example, to be about three times higher than that of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C2C1Im][Tf2N]. In order to explain these macroscopic changes upon methylation we investigated the vibrational as well as the magnetic resonance structure of [Tf2N]- salts involving the cations 1-ethyl-3-methylimidazolium [C2C1Im]+, 1-ethyl-2,3-dimethylimidazolium [C2C1C1Im]+, 1-butyl-3-methylimidazolium [C4C1Im]+, and 1-butyl-2,3-dimethylimidazolium [C4C1C1Im]+ by means of Fourier-transform infrared (FTIR), Raman and 13C NMR as well as 1H NMR spectroscopy aiming a better microscopic understanding of the cation–anion interaction. To reveal the impact of methylating the C2 position and changing the alkyl side chain length of the imidazolium a detailed assignment of the individual peaks is followed by a comparative discussion of the spectral features also considering already published work. Our spectroscopic findings deduce electron density changes leading to changes in the position and strength of interionic interactions and reduced configurational variations. Both facts are represented on a macroscopic level by the viscosity and melting point. Therefore changes on a macroscopic level clearly express molecular alterations which in turn can be observed using spectroscopic methods as Raman, IR and NMR.